Konsep Biaya dan Relevansinya dalam Pengambilan Keputusan Startup Digital: Perspektif Akuntansi Manajerial dan Ekonomi Syariah - Arlinta Prasetian Dewi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2026)
Digital startups operate in a fast-changing, competitive, and uncertain business environment, requiring companies to make strategic decisions quickly and accurately. In this context, cost concepts in managerial accounting play an important role in supporting business decision-making processes. This study aims to analyze the application of cost concepts in startup digital decision-making from the perspectives of managerial accounting and Islamic economics. The research uses a qualitative descriptive approach based on literature studies by examining various academic references related to relevant costs, opportunity costs, differential costs, startup digital management, managerial accounting, and Islamic economic principles. The findings indicate that the application of relevant cost concepts helps startups determine efficient and strategic business alternatives in activities such as outsourcing, pricing strategies, business pivoting, and human resource management. From the managerial accounting perspective, cost information functions as a strategic tool for planning, controlling, and evaluating business decisions. Meanwhile, from the Islamic economics perspective, the use of cost concepts must not only focus on efficiency and profitability but also emphasize justice, transparency, social responsibility, and public benefit (maslahah). The integration of managerial accounting and Islamic economic principles in cost management can support digital startups in creating adaptive, ethical, and sustainable business decisions amid the challenges of the modern digital economy.